Unified predictive flux control for EESM, IM, PMSM and SyRM - Stos, Johannes; Geier, Leonard; Karayel, Akif; Decker, Simon; Liske, Andreas; Hiller, Marc (IEEE Energy Conversion Congress and Exposition, 2023)
This paper describes a new method for a high dynamic and nonlinear unified model predictive control of induction motors (IM), permanent magnet synchronous machines (PMSM), synchronous reluctance machines (SyRM) and electrically excited synchronous machines (EESM) using the same control algorithm. This is enabled by a unified nonlinear machine model that allows the described machines to be modelled and controlled basically as a variation of the EESM. This allows simple and fast adaptation of drive systems to new motors as only the model parameters of the control system need to be adjusted. By eliminating the need to customize the code base for individual machine types, software platforms can be simplified to handle even large product ranges cost-effectively.